Feline microRNAome in ovary and testis: Exploration of in-silico miRNA-mRNA networks involved in gonadal function and cellular stress response - Amelkina, Olga; Silva, Andreia M. da; Silva, Alexandre R.; Comizzoli, Pierre (Frontiers in Genetics, 2022)
The aim of the study was to perform the first in-depth analysis of miRNAs in ovarian and testicular tissues of the domestic cat, a critical biomedical model. Specifically, potential miRNA involvement was explored in gonadal function, testis development, and cellular stress response. We performed miRNA-sequencing on 20 ovarian and 20 testicular samples from 15 cats, including different ages and tissue conditions. Using fresh tissues (n = 15), we confirmed gonadal expression of 183 miRNA precursors and discovered additional 52 novel feline candidate precursors. We integrated the mRNA data from our previous study on the same age and condition groups to create in-silico miRNA-mRNA networks and their functional enrichment allowing comprehensive exploration into possible miRNA functions in cat gonads. Clusters of miRNAs united by shared differentially expressed mRNA targets are potentially involved in testicular development and spermatogenesis. MicroRNAs could play a significant role in ovarian tissue response to stress from microwave-assisted dehydration, with smaller roles in cellular response to vitrification in both ovary and testis. This new list of miRNAs with potential function in cat gonads is a major step towards understanding the gonadal biology, as well as optimizing fertility preservation protocols.